Perilaku Memilih Pemegang Kartu Tani pada Pemilihan Gubernur Jawa Tengah 2018 Kabupaten Semarang (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2019)
The benefits of the research to analyze the factors that influence the behavior of selecting farmers who hold farmers card in the Election Governor of Central Java 2018 in Semarang Regency. The research method is a quantitative research that is supported by a descriptive approach with a qualitative approach. Quantitative data collection techniques using surveys and qualitative collection using in-depth interview and documentation. The results of the research and discussion of this study indicate that the behavior of farmers is influenced by four factors, namely sociological, psychological, rational, and coginitive domains. For sociological factors, because is influended by friendship or family relations. Psychological factors because likes to the figure of Ganjar. Incentive factor because they are often assisted by Ganjar supporters. Cognitive domain factors, farmers choose because kindness from the presence of farmer cards. Farmer card holders give their votes because emotional ties to respected figures in their neighborhood who are members of campaigners. But there was also the phenomenon abstentions in Bancak District due to apathy towards the existence of a peasant card policy. The conclusion is that farmers who hold farmers card in Semarang Regency prefer Paslon 1 Ganjar Pranowo-Taj Yasin.